Long-term survival in thymic carcinoma with postoperative pleural dissemination - Toru Kimura; Masahiko Higashiyama; Keiichiro Honma; Harumi Nakamura; Tomohiro Maniwa; Jiro Okami (Surgical Case Reports, 2021)
Abstract Background We report a patient with thymic squamous cell carcinoma who underwent multiple rounds of surgical resection and definitive radiotherapy for both primary tumor and postoperative recurrence. However, the patient remains well and healthy 18 years after initial diagnosis. Since long-term survival after postoperative recurrence of thymic carcinoma is extremely rare, we also present her immunohistochemical staining results, which suggested indolent disease. Case presentation A 42-year-old woman with thymic squamous cell carcinoma underwent en bloc resection of the tumor and thymus gland. Pleural dissemination was noted in the right thoracic cavity 3, 10, and 16 years postoperatively. Where possible, the nodules were resected surgically: during the postoperative 3rd and 16th years. Definitive radiotherapy was administered for all nodules that could not be excised during the postoperative 3rd and 10th years. Disease-free survival is 25 months. Conclusions Local control of pleural dissemination may be beneficial in the treatment of postoperative recurrence of thymic carcinoma in limited cases of indolent disease.